Bionomics and Control of Salai Defoliator Rhesala (Paparna) Imparata Walker (Lepidoptera : Noctuidae) - Misra, Ram Mohan; Singh, Pratap (Indian Forester, 1993)
Salai defoliator Rhesala imparata Walker is a new pest record on Boswellia serrata. The moth appeared in January and oviposited in clusters. Incubation period was 3-5 days, larval period ranged 15-28 days, pupal period 5-10 days in August and 11-22 days in October-November. Life cycle was completed in 23-55 days. A nuclear polyhedrosis virus was recorded from the larva of R. imparata at Barnawapara. A parasite wasp was also recorded from larvae of R. imparata.